PROFIL KEPATUHAN PENGGUNAAN OBAT HIPOGLIKEMIK ORAL GLIBENKLAMID (Pada Pasien Diabetes Mellitus Tipe 2 di Puskesmas Kedungkandang Malang) - Masita Rinaldia Hidajah R (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Indonesia is one of the developing countries and listed as number seven rank in the world as a country with problems with the disease. Increasing prosperity in developing countries and changes in lifestyle lead to increased prevalence of degenerative diseases one of them with diabetes mellitus (DM). Patients with diabetes mellitus need support from other families also need support from professionals in the health sector such as doctors, nurses, pharmacy. With the support - support that is given so that it can improve the quality of life of people and with diabetes mellitus. This study aimed to profile the compliance in the use of oral hypoglycemic glibenclamide. This research was conducted using descriptive research design. Samples were taken from patients with type 2 diabetes mellitus patients in health centers Kedungkandang Malang. Research done by giving questionnaires and visits from the remaining drug count glubenklamid obtained. From the description of the questions is obtained for 73.3% never received an explanation from the pharmacist and 70% of patients did not request an explanation from the pharmacist. Amounted to 86.7% of patients knew the use of drug glibenclamide. 56.7% of patients returned to the clinic every drug out and amounted to 50% of patients received support from family. Patients using the drug each day with a percentage of 53.3% and 66.7% of information on how to read and drink a patient using the drug in accordance with the percentage dose of 70% and use drug the morning before eating with a percentage of 46.7% and 63.33% and patients who never experienced drug side effects of 76.7%. From the calculation of drug remaining is calculated from the sum of all the samples showed results of 83.3% compliance. So the usage of drug compliance glibenclamide in patients with type 2 Diabetes in Primary Health Care Melllitus Kedungkandang Malang by 83.3%.